2013
DOI: 10.4028/www.scientific.net/amr.829.683
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Nano-Structured Multiferroic Bismuth Ferrite Produced via Solid State Reaction Route

Abstract: Multiferroic bismuth ferrite, BiFeO3, was synthesized via conventional solid-state reaction method using Bi2O3, Fe2O3 as starting materials. Effects of Bi2O3/Fe2O3 molar ratio and calcination temperature on the phase composition, morphology and magnetic properties of produced powders were systematically studied using XRD, FESEM/EDS and VSM techniques, respectively. The results revealed that BiFeO3 phase with rhombohedral R3c structure with a mean particle size of 40 nm was formed in the sample processed with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Gd-NGO has also been shown to effectively carry the anthracycline anticancer drug epirubicin (EPI). Conjugation of MIRLET7G and EPI with Gd-NGO (Gd-NGO/ Let-7g/EPI) enhanced the inhibition of cancer (glioblastoma) cell growth in comparison with the single conjugates (Gd-NGO/Let-7g and Gd-NGO/EPI) [76].…”
Section: Clinical Relevance Of Cell-free Mirnas In Ovarian Cancermentioning
confidence: 99%
“…Gd-NGO has also been shown to effectively carry the anthracycline anticancer drug epirubicin (EPI). Conjugation of MIRLET7G and EPI with Gd-NGO (Gd-NGO/ Let-7g/EPI) enhanced the inhibition of cancer (glioblastoma) cell growth in comparison with the single conjugates (Gd-NGO/Let-7g and Gd-NGO/EPI) [76].…”
Section: Clinical Relevance Of Cell-free Mirnas In Ovarian Cancermentioning
confidence: 99%
“…Whereas the other samples are polycrystallines with many peaks corresponding to the undesired phase a long with the perovskite BiFeO 3 . Generally, the undesired phase attributed to Fe or Bi rich phases, Bi 2 Fe 4 O 9 and Bi 25 FeO 40 were routinely observed as shown in previous results [37]. It is very difficult to maintain the right stoichiometry in the grown BFO films due to the high volatility of Bismuth [38].…”
Section: Influence Of Oxygen Pressurementioning
confidence: 74%
“…Kojima et al [61] have prepared fully PEGylated PAMAM dendrimers loaded with Gd-diethylenetriamine pentaacetic acid (DTPA). For conjugation of Gd-DTPA to the side chain, Lysine (Lys) was attached before the PEG modification [62]. Their results showed that PEGylation of a Gd-labeled PAMAM dendrimer decrease the relaxivity and plasma clearance, and variations susceptibility to temperature.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%